2019
DOI: 10.1111/jog.13946
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of neutrophil to lymphocyte ratio in prediction of medical treatment failure for tubo‐ovarian abscess

Abstract: Aim We aimed to compare the neutrophil‐to‐lymphocyte ratio (NLR) in tubo‐ovarian abscess (TOA) patients who responded to medical treatment or who underwent surgical intervention due to medical treatment failure. Methods The files of the patients, hospitalized in our Obstetrics and Gynecology Department with TOA diagnosis between August 2015 and December 2017, were evaluated retrospectively. The conservative management group was comprised of 38 of the 81 patients (46.9%) who responded to sole medical treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Early surgical intervention can reduce morbidity and mortality in TOA patients who do not respond to antibiotics. Several studies of demographic and clinical characteristics associated with antibiotic treatment failure in TOA patients have shown that the TOA size and age of the patient are signi cantly related and proportional to the need for surgical treatment (6)(7)(8)(9)(10)(11). Early recognition of a patient's risk of antibiotic treatment failure alerts clinicians to the need to change the treatment strategy, thereby reducing acute and longterm complications of TOA.…”
Section: Discussionmentioning
confidence: 99%
“…Early surgical intervention can reduce morbidity and mortality in TOA patients who do not respond to antibiotics. Several studies of demographic and clinical characteristics associated with antibiotic treatment failure in TOA patients have shown that the TOA size and age of the patient are signi cantly related and proportional to the need for surgical treatment (6)(7)(8)(9)(10)(11). Early recognition of a patient's risk of antibiotic treatment failure alerts clinicians to the need to change the treatment strategy, thereby reducing acute and longterm complications of TOA.…”
Section: Discussionmentioning
confidence: 99%
“…Early surgical intervention can reduce morbidity and mortality in TOA patients who do not respond to antibiotics. Several studies of demographic and clinical characteristics associated with antibiotic treatment failure in TOA patients have shown that the TOA size and age of the patient are significantly related and proportional to the need for surgical treatment (6)(7)(8)(9)(10)(11). Early recognition of a patient's risk of antibiotic treatment failure alerts clinicians to the need to change the treatment strategy, thereby reducing acute and long-term complications of TOA.…”
Section: Discussionmentioning
confidence: 99%
“…Yildirim et al reported that WBCs and neutrophils were elevated in TOA patients, and neutrophils were elevated even when the WBC count was normal (13); they also found that lymphocytes were relatively decreased, resulting in an increase in the neutrophilto-lymphocyte ratio (NLR). Alay et al reported that neutrophil counts were significantly higher in TOA patients with no response to medication and that the NLR could be used to predict non-response to medication in TOA patients (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 It has been found that elevated ca125 is related with failure of conservative parenteral antibiotic therapy for TOA, but further prospective studies are necessary to evaluate this finding. Last year Alay et al 43 presented the neutrophil-to-lymphocyte ratio (NLR) and age as significant indicators in the prediction of medical treatment failure in TOA patients. Unfortunately, to now, there are not enough data to suggest an accurate scoring system which could guide the clinicians to choose the better approach for each different case.…”
Section: Prognosismentioning
confidence: 99%